2021
DOI: 10.1002/mnfr.202100626
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Suppresses Amyloid β Levels and Alleviates Cognitive Impairment by Inhibiting APP Cleavage and Preventing Neurotoxicity in 5XFAD Mice

Abstract: Scope The consumption of green tea is considered to be associated with a lower incidence of neurodegenerative diseases. In the present study, it is investigated the role of amyloid precursor protein cleavage, glial cell activation, neuroinflammation, and synaptic alterations in the protective effects of green tea against the amyloid β (Aβ) accumulation and cognitive impairment. Methods and Results 5XFAD mice are treated with green tea extract (GTE) for 8 or 16 weeks. Barnes maze and Y maze testing demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Compared with WT, the IFN-γ level in 5xFAD mice was increased for the first time in this study. In in vitro, IL-5 prevented tau hyperphosphorylation and apoptosis induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) through the JAK2 signaling pathway (57). G-CSF is a growth factor associated with AD improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with WT, the IFN-γ level in 5xFAD mice was increased for the first time in this study. In in vitro, IL-5 prevented tau hyperphosphorylation and apoptosis induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) through the JAK2 signaling pathway (57). G-CSF is a growth factor associated with AD improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study compared the neuroprotective effects of green, red, and black tea, and found that green tea supplementation demonstrated the best effect in an Alzheimer-like rat model [ 9 ]. Recent research demonstrated that green tea extracts could significantly suppress amyloid β levels and alleviate cognitive impairment at a daily consumption of 700 mg/kg in a mouse model [ 22 ]. Our finding is consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a study showed that EGCG-rich green tea exerted beneficial effects on dextran sulfate sodium (DSS)-treated ulcerative colitis mice by ameliorating malignant inflammatory stressors and attenuating tumorigenic progression (Diwan & Sharma, 2022). Additionally, the administration of EGCG-rich green tea extract suppressed the brain amyloid β levels and improved cognitive function in genetically engineered AD mouse models (Kan et al, 2021). The extract of EGCG-rich tea (EGCG content accounted for 13.91% of DW) was reported to exert potent anti-tumor effects, potentiate the anti-tumor effects of specific drugs, and alleviate the hepatic and renal toxicities of drugs in BALB/c-nu nude mice (Chen, 2015).…”
Section: Health Benefits Of Egcg-rich Tea Productsmentioning
confidence: 99%